Investigating the Effect of Microcystins on the Transcriptomics of Hepatopancreas in Penaeus vannamei Using Reverse-Gavage - Haiqing YUAN; Rongsheng JIN; Baoran WANG; Daiqiang CHEN; Shuangyong ZHANG; Zhiqiang CHANG (Progress in Fishery Sciences)
Whiteleg shrimp (Penaeus vannamei) significantly contributes to the Chinese aquatic product market. However, continuous intensification has led to eutrophication in water bodies, resulting in frequent cyanobacterial blooms. These blooms release microcystins, which pollute water and cause substantial death rates among cultured organisms, posing a serious threat to agriculture and public health. Microcystin-LR (MC-LR) is the most prevalent and highly toxic variant. MC-LR is toxic to aquatic organisms and impacts terrestrial organisms and human health in several ways. These significant effects have attracted widespread attention in the academic community. MC-LR is hepatotropic and accumulates in the hepatopancreas after entering the body. Numerous reports have described the toxicological effects of MC-LR from various perspectives; however, its potential biological processes remain highly complex and may involve multiple signaling pathways in P. vannamei.Most experiments investigating the acute exposure of shrimp to compounds use blood sinus injection or intramuscular injection. However, these methods can potentially cause tissue damage and change immune indicators. Reverse-gavage reduces tissue damage and directly affects the hepatopancreas. Furthermore, reverse-gavage can also simulate reactions to toxic substance under natural conditions. First, the MC-LR solution was mixed with red edible dye, which was then slowly dripped into the anal cavity of the experimental group using an automatic pipette. The inoculation solution entered the midgut from the hindgut and ceased when the red color reached the hepatopancreas. After 24 h, the cephalothoraxes was dissected to obtain the hepatopancreas tissue. Subsequently, transcriptome sequencing technology was used to identify the differentially expressed genes related signaling pathways and metabolic pathways in the hepatopancreas of P. vannamei under MC-LR treatment. The results of the transcriptome sequencing were validated using quantitative real-time PCR.MC-LR induced significant differential expression of 1 994 genes compared to the control group. Of these, 1 164 were up-regulated and 830 were down-regulated. The differentially expressed genes were categorized based on biological processes, cellular components, and molecular functions using the Gene Ontology (GO) database, resulting in 33 functional entries. Kyoto Encyclopedia of Genes and Genomes (KEGG) database analysis revealed that the transcriptome of P. vannamei had 240 differentially expressed genes annotated across six categories: metabolism, genetic information processing, environmental information processing, cellular processes, biological systems, and human disease. The main metabolic pathways included carbohydrate metabolism, lipid metabolism, protein translation, signal transduction, cell growth and apoptosis, transport and catabolism, immune system, and endocrine system. GO functional enrichment analysis revealed that the functions of significantly differentially expressed genes were primarily enriched in catalytic activity, heterocyclic compound binding, carbohydrate derivatives, small molecule binding, protein folding, and RNA metabolism. Among the top 20 enriched KEGG pathways, the ribosome biosynthesis pathway was significantly enriched. Additionally, pathways related to lipids, atherosclerosis, endoplasmic reticulum protein processing, and purine metabolism were also enriched. The number of differentially expressed genes was more than those of the untreated control. These pathways may be involved in metabolism, environmental information processing, and cellular processes of P. vannamei under microcystin stress. Consequently, the top ten genes with the most significant differential expression were further screened. Notably, zinc finger protein 761-like expression was down-regulated. Differential gene expression statistical analysis indicated that several genes belonging to the zinc finger protein family were significantly down-regulated. This suggests their potential involvement in the microcystin response of P. vannamei.In conclusion, this study provides a methodological reference for shrimp exposure experiments and the molecular regulation mechanism of P. vannamei in response to microcystins. However, the reverse-gavage method requires improvement, and a methodological comparison of different approaches is also necessary to understand the advantages and disadvantages of reverse-gavage methods. Simultaneously, further verification of the differentially expressed genes is required to determine their close relationship with the response of P. vannamei to microcystin stress. These findings will enable in-depth exploration and improvement of the toxicological mechanism in P. vannamei.